2020
DOI: 10.1177/1535370220953386
|View full text |Cite
|
Sign up to set email alerts
|

CD248+CD8+ T lymphocytes suppress pathological vascular remodeling in human thoracic aortic aneurysms

Abstract: Aortic aneurysms are characterized by vascular inflammation, neovascularization, and extracellular matrix destruction of the aortic wall. Although experimental studies indicate a potential role of CD248 in microvessel remodeling, the functions of CD248 in human vascular pathologies remain unexplored. Here we aimed to study how CD248 interferes with pathological vascular remodeling of human aortic aneurysms. Immunofluorescent staining showed that CD248 expression was mainly localized in the CD8+ T cells infiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Furthermore, endosialin-knockout mice were reported to be protected against arterial thrombosis [6]. An immunofluorescence analysis also showed increased endosialin expression and infiltrating CD8 T cells in aortic aneurysm specimens, suggesting a role of endosialin in vascular remodeling [3].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, endosialin-knockout mice were reported to be protected against arterial thrombosis [6]. An immunofluorescence analysis also showed increased endosialin expression and infiltrating CD8 T cells in aortic aneurysm specimens, suggesting a role of endosialin in vascular remodeling [3].…”
Section: Discussionmentioning
confidence: 96%
“…Since endosialin is suggested to play a role in the progression of atherosclerosis [3,4,6], we hypothesized that plasma endosialin levels in patients with CAD would be high. Our present study is the first to report plasma endosialin levels in patients with CAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the phenotypes of the T CD4+, CD8+, and B cell subpopulations were not analyzed in our study, as well as gene expression and cytokine production. In fact, it has recently been reported that the cytokines produced by CD4+ and CD8 + T-lymphocytes and their subsets, such as CD248+ CD8+ T cells [47], play a causative role in the initiation and progression, as well as in the suppression, of aorta remodeling associated with onset of pathological conditions, such as aorta dilatation and aneurysm development [46,48]. Of note, for example, is the role of the abovementioned CD248+ CD8 + T [47] cells subset and its cytokine profile, that has been recently demonstrated to suppress the pathological vascular remodeling in human TAAA.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has recently been reported that the cytokines produced by CD4+ and CD8 + T-lymphocytes and their subsets, such as CD248+ CD8+ T cells [47], play a causative role in the initiation and progression, as well as in the suppression, of aorta remodeling associated with onset of pathological conditions, such as aorta dilatation and aneurysm development [46,48]. Of note, for example, is the role of the abovementioned CD248+ CD8 + T [47] cells subset and its cytokine profile, that has been recently demonstrated to suppress the pathological vascular remodeling in human TAAA. This underlines the imperative necessity to investigate the type of T subsets in the aneurysm aorta tissues and their cytokine profile.…”
Section: Discussionmentioning
confidence: 99%